Brill's companion to the reception of Herodotus in antiquity and beyond - Priestley, Jessica; Zali, Vasiliki (Brill's companions to classical reception, 2016)
"Brill's Companion to the Reception of Herodotus in Antiquity and Beyond offers new insights on the reception and cultural transmission of one of the most controversial and influential texts to have survived from Classical Antiquity. Herodotus' Histories has been adopted, adapted, imitated, contested, admired and criticized across diverse genres, historical periods, and geographical boundaries. This companion, edited by Jessica Priestley and Vasiliki Zali, examines the reception of Herodotus in a range of cultural contexts, from the fifth century BC to the twentieth century AD. The essays consider key topics such as Herodotus' place in the Western historiographical tradition, translation of and scholarly engagement with the Histories, and the use of the Histories as a model for describing and interpreting cultural and geographical material. Contributors are: Eran Almagor, Christopher A. Baron, Benjamin Earley, Adam Foley, Vivienne Gray, Greta Hawes, Kinga Kosmala, Dennis Looney, John Marincola, Neville Morley, Heather Neilson, Jessica Priestley, Félix Racine, Andreas Schwab, Benjamin Eldon Stevens, Olga Tribulato, Marek Wecowski, and Vasiliki Zali"--
Includes bibliographical references and index
Keywords: Herodotus -- History; Herodotus -- Appreciation; Aufsatzsammlung; Konferenzschrift -- 2013 -- Bristol; Geschichte; Rezeption; Herodotus